Strategi Pencegahan Bullying melalui Sosialisasi dan Pembentukan Karakter Positif di SD Negeri Kadipaten - Nurcholis, Herlan; Fatimah, Dewi; Mahfuri, Humaira Vidiani; Zahra, Lulu Wafidatuz; Pranawa, Aish Tabriza Risang; Widad, Fahmi Ainul; Gusti, Ahmad Dzaky Ridhaning; Milak, Akmal Khoirul; Putra, Dhimaz Raihan Fajari Irwanto; Fadillah, Roojil (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
In the school environment, bullying is one of the problems that often occurs and can have a negative impact on students' psychological and academic development. Lack of awareness and understanding of the impact of bullying causes this behavior to continue to be repeated, both in physical, verbal, and social forms. Many students at SDN Kadipaten have become victims to experience a decrease in confidence, emotional disturbances, and fear to go to school. Therefore, effective prevention and handling efforts are needed so that the school environment becomes safer and more comfortable for all students. In response to these problems, the KKN work program of the 196 UMY group aims to prevent and overcome bullying in SD Negeri Kadipaten through socialization and the formation of positive character. This activity includes initial observation of student behavior, socialization about the impact of bullying, and anti-bullying campaigns through poster making and educational video screening. The method used in this program uses a participatory approach with various strategies to achieve the goal of preventing and handling bullying in SD Negeri Kadipaten. One of the main methods is interviews with teachers, which aim to understand social dynamics in schools, interactive discussions with students to instill empathy, as well as the installation of posters as visual reminders. With the involvement of various parties, it is hoped that bullying prevention efforts can run continuously. The results of this activity showed a significant increase in students' understanding of bullying. Before the program started, only 40% of students understood the concept of bullying, but after socialization, this figure increased to 85%. Active participation in interactive discussions also increased by 70%, indicating an increase in student awareness. In addition, the number of reports of bullying incidents in schools decreased within a month of the program, and 75% of students who were previously reluctant to report bullying are now more willing to ask teachers or schools for help. This program is expected to be the first step in building a sustainable anti-bullying culture in schools with full support from the school and the surrounding community. The sustainability of this program can be improved by holding regular socialization sessions, as well as providing reporting facilities that are easily accessible to students. Thus , schools can become a safer, more comfortable environment, and support children’s development optimally.